Features of examination of temporary disability in the dental practice (Эндодонтия Today, 2020)
The article deals with issues related to the examination of temporary disability in the dental practice. The basic legal documents on the organization of disability examination, indications and procedure for issuing certificate of incapacity are described in detail in dental diseases. The algorithm of its issuance in the dental practice in compliance with the terms of disability. Submitted by Statistics issuing leaflets temporary disability medical institutions of the Republic of Tatarstan, including dental organization.